Exploring Indoor Air Pollution Exposure During Pregnancy and Risk of Low Birth Weight in Seberang Ulu 1, Palembang (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2019)
Adverse birth outcomes are determined by a complex combination of genetic, social, and environmental factors. Numerous studies have concluded an association exists between air pollution and low birth weight (LBW). This case-controlled study aimed to analyze the association by using 38 cases (mothers of LBW infants) and 40 controls (mothers of normal birth weight infants) in Seberang Ulu 1, Palembang City. Primary data related to indoor air pollution exposure during pregnancy was collected via structured interviews. The data was analyzed by performing chi-square and multiple logistic regressions within a risk factor model. Exposure to indoor air pollution during pregnancy was associated with the occurrence of LBW (chi-square test, p-value: 0.012, OR 3611 [95% CI 1.415 to 9.215]). No variables were found to have an interaction with the effects of indoor air pollution exposure during pregnancy and the occurrence of LBW. Exposure to indoor air pollution during pregnancy had the most significant impact on LBW occurrences after controlling for maternal age during pregnancy (multiple logistic regression, p-value: 0.019, OR 3.19 [95% CI 1, 21-8.406]).